Rain of ash : Roma, Jews, and the Holocaust - Joskowicz, Ari, 1975- 1975- (Princeton University Press, 2023)
"A major new history of the genocide of Roma and Jews during World War II and their entangled quest for historical justiceJews and Roma died side by side in the Holocaust, yet the world did not recognize their destruction equally. In the years and decades following the war, the Jewish experience of genocide increasingly occupied the attention of legal experts, scholars, educators, curators, and politicians, while the genocide of Europe's Roma went largely ignored. Rain of Ash is the untold story of how Roma turned to Jewish institutions, funding sources, and professional networks as they sought to gain recognition and compensation for their wartime suffering.Ari Joskowicz vividly describes the experiences of Hitler's forgotten victims and charts the evolving postwar relationship between Roma and Jews over the course of nearly a century. During the Nazi era, Jews and Roma shared little in common besides their simultaneous persecution. Yet the decades of entwined struggles for recognition have deepened Romani-Jewish relations, which now center not only on commemorations of past genocides but also contemporary debates about antiracism and Zionism.Unforgettably moving and sweeping in scope, Rain of Ash is a revelatory account of the unequal yet necessary entanglement of Jewish and Romani quests for historical justice and self-representation that challenges us to radically rethink the way we remember the Holocaust"--